Quest to develop a standard screening method for urothelial carcinoma using liquid-based cytology (The Paris System) and CK20 - Kavita Jain; Chhanda Datta; Moumita Sengupta; Dilip Kumar Pal; Uttara Chatterjee (Wolters Kluwer Medknow Publications, 2023)
Background: Bladder cancer, the most common malignancy of the urinary tract is a leading cause of morbidity and mortality. But cystoscopy, which is till now the mainstay of screening, is an invasive, high-cost method with low sensitivity especially for flat lesions. Aim: To find a non-invasive and effective screening method with liquid-based cytology (LBC) using The Paris System (TPS) and CK20 immunocytochemistry. Materials and Methods: It was a prospective study including the patients with clinical or cystoscopic diagnosis of urinary bladder space occupying lesions (SOL). Both conventional (CC) and liquid-based cytology slides were prepared from urine samples. Slides were evaluated by two trained pathologists and categorized according to TPS guidelines. CK20 immunocytochemistry (ICC) was also performed. Consequent formalin-fixed paraffin embedded sections were blindly examined by another pathologist and was taken as gold standard for comparison. Statistical Analysis: All the statistical analysis were done using MedCalc version 15.8 [Mariakerke, Belgium: MedCalc Software 2015]. Results: The study included 150 cases with a mean age of 62.4 years. Five cases revealed unsatisfactory smears. Rest of the cases were categorized as the following: 18.1% as NH-GUC, 8% as LGUN, 22.1% as AUC, 15.4% as SH-GUC, 32.9% as HGUC. Kappa value of CC and LBC were strong (0.854). LBC alone showed very low specificity (58%) and PPV (74.8%) which improved on application of ICC (specificity: 97.4%, PPV: 96.3%). Conclusion: We conclude that CK20 ICC offers potential for accurate, non-invasive detection and surveillance of bladder cancer and is a better tool when combined with liquid-based cytology, reported using The Paris System.